2022
DOI: 10.1115/1.4053601
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Local and Averaged Air-Side Heat Transfer Coefficients on Fin-and-Tube Heat Exchangers Obtained With Experimental and Numerical Methods

Abstract: Numerical methods are often used to obtain two-dimensional air-side heat transfer coefficients (HTCs) on heat exchanger fin surfaces. The model's accuracy is usually verified through averaged HTCs by comparing to published experimental results. However, substantial disagreement is not uncommon and can hardly be explained by averaged HTCs. This study focuses on comparing experimental, local air-side HTCs to numerical ANSYS Fluent results. A mass transfer experimental method was employed to obtain HTC distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A recent study reports that, despite variations in local values, the average values of the performance indices derived from numerical simulations of finned-tube heat exchanger closely match the experimental values. 18 Zdanski et al 19 carried out an experimental study on an inline tube bank with delta winglets on the upstream, and reported a correlation for the average Nusselt number. Here, it is interesting to know that the winglets can be integrated in a finned-tube bank in two different ways, 2 either with its leading points spread apart or its trailing points spread apart, where former is referred to as “toe-out” arrangement (also called common-flow up arrangement) and the latter is referred to as “toe-in” arrangement (also called common-flow down arrangement).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reports that, despite variations in local values, the average values of the performance indices derived from numerical simulations of finned-tube heat exchanger closely match the experimental values. 18 Zdanski et al 19 carried out an experimental study on an inline tube bank with delta winglets on the upstream, and reported a correlation for the average Nusselt number. Here, it is interesting to know that the winglets can be integrated in a finned-tube bank in two different ways, 2 either with its leading points spread apart or its trailing points spread apart, where former is referred to as “toe-out” arrangement (also called common-flow up arrangement) and the latter is referred to as “toe-in” arrangement (also called common-flow down arrangement).…”
Section: Introductionmentioning
confidence: 99%
“…These studies usually describe the local heat exchange and often compare it to the average HTC. Che and Elbel [14] showed the experimental and numerical determination of heat transfer coefficients (HTCs) using the absorption-based mass transfer method. This study showed that the HTC value in the first row of FHE compared to the second row of FHE can be 30% higher.…”
Section: Introductionmentioning
confidence: 99%
“…There are well-known commercial computational fluid dynamics (CFD) programs. The most popular are the following: ANSYS CFX/Fluent [7,8] and COMSOL Multiphysics [9]. In [7] the authors have considered four-row finned-tube heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…The main result was the proposition of new correlations for the air-side Nusselt number for the four-row finned tube heat exchanger. ANSYS Fluent software has been used in [8]. The study focuses on comparing experimental heat transfer coefficients on the local air side with numerical results obtained with the help of the ANSYS Fluent software.…”
Section: Introductionmentioning
confidence: 99%